2017
DOI: 10.5005/jp-journals-10005-1405
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ion Diffusion from Calcium Hydroxide with Various Herbal Pastes through Dentin

Abstract: AimThe aim of this study was to evaluate the diffusion ability of ions through dentinal tubules of different nonalcoholic calcium hydroxide-containing herbal pastes and compare it with the calcium hydroxide paste prepared with saline.Materials and methodsA total of 36 single-rooted premolar teeth were used in this study. The tooth crowns were removed and the root canals were prepared. Depending on the vehicle to be used for preparing calcium hydroxide pastes, six groups were made: Group I: Ca(OH)2 saline paste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Besides permitting diffusion of the Ca(OH) 2 , the vehicle can enhance the antimicrobial capacity of the paste. [ 21 ] According to Gomes et al ,[ 22 ] chlorhexidine can be used as a vehicle for attempting an increase in the antimicrobial property to be effective against aerobic and facultative anaerobic microorganisms, Gram-positive and Gram-negative microorganisms, yeasts, and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Besides permitting diffusion of the Ca(OH) 2 , the vehicle can enhance the antimicrobial capacity of the paste. [ 21 ] According to Gomes et al ,[ 22 ] chlorhexidine can be used as a vehicle for attempting an increase in the antimicrobial property to be effective against aerobic and facultative anaerobic microorganisms, Gram-positive and Gram-negative microorganisms, yeasts, and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to improve the effectiveness of calcium hydroxide pastes have been proposed using chemicals such as p-chlorophenol and Chlorhexidine [37]. Dausage et al also supported this finding in 2017, who reported that the diffusion ability of calcium hydroxide ions through dentinal tubules is facilitated by the addition of herbs [38]. It has been recognized that long-term exposure to calcium hydroxide alone decreases the strength of root dentin and changes its physical properties, while a mixture of calcium hydroxide with other materials decreases it is an adverse effect on root dentine [39].…”
Section: Discussionmentioning
confidence: 97%
“…8 Owing to their safety and ability to combat new developing drug resistant pathogens, herbal preparations are always welcome in presentday science. 9 There are insufficient scientific reports that indicate the antimicrobial activities of herbal extracts mixed with endodontic root canal sealers. Hence, the aim of the study was to evaluate and compare the antimicrobial efficacy of endodontic sealers of different bases mixed with herbal extracts.…”
Section: Discussionmentioning
confidence: 99%